ANALISIS MINAT BELAJAR SISWA KELAS V SEKOLAH DASAR PADA MATA PELAJARAN MATEMATIKA - Rosy Vania, Nadya; Nuriyanti, Risma; Indriati Widyaningsih, Yennie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning interest is one of the psychological factors that plays an important role in the success of learning at the elementary school level. However, the reality in the field shows that students' interest in the subject of Mathematics tends to be low. This study aims to describe the forms of learning interest of fifth-grade students in the subject of Mathematics, identify the factors that influence it, and analyze the role of teachers in increasing that interest. This study uses a descriptive qualitative approach, with data collection techniques in the form of observation, interviews, and questionnaires involving 30 students and 1 teacher at SDN 2 Karangmulya. The results of the study indicate that most students show low learning interest, characterized by a lack of enthusiasm, participation, and concentration in the subject of Mathematics. The factors causing students' low learning interest include a lack of variation in the teacher's teaching models or methods, the lack of use of engaging learning media, as well as students' perception that Mathematics is difficult and boring. On the other hand, the use of visual media such as videos and images has been proven to be able to increase students' interest. This study concludes that improving students' interest in learning Mathematics requires a more interactive teaching approach, the use of varied learning media, as well as attention to students' psychological conditions and learning environment. These findings are expected to serve as a basis for developing more effective and contextual learning strategies at the elementary school level.